CFD modeling of gas-particles flow in a circulating fluidized G-Volution gasification reactor. (August 2018) - Hassen, Walid; Dhrioua, Maryem; Kolsi, Lioua; Anbumalar, Veerabathiran; Al-Rashed, Abdullah A.A.A.; Borjini, Mohamed N.
Highlights: Cold flow of a gas–solid mixture in a G-Volution is studied numerically. The Eulerian–Eulerian fluid model is adopted. The effect of different parameters is investigated. Abstract: Numerical simulations of the cold flow of a gas–solid mixture in a G-Volution circulating dual gasification reactor are conducted by using the commercial software package ANSYS FLUENT. Isothermal non-reactive, turbulent, unsteady gas–solid flow is assumed and the Eulerian–Eulerian fluid model is adopted. The effect of restricted cross sections on the pressure gradient and the solids holdup in the fuel reactor of this Circulating Fluidized G-Volution Gasification dispositive is investigated. Computation of the reactor without internals is also conducted for comparison. In addition, segregation in a fluidized binary biomass –sand bed is considered for different inlet velocities. Graphical abstract: Image, graphical abstract